Effect of the SGLT2 Inhibitor Dapagliflozin on Potassium Levels in Patients with Type 2 Diabetes Mellitus: A Pooled Analysis. Issue 1 (March 2016) - Yavin, Yshai; Mansfield, Traci; Ptaszynska, Agata; Johnsson, Kristina; Parikh, Shamik; Johnsson, Eva
Abstract Introduction Hyperkalemia risk is increased in diabetes, particularly in patients with renal impairment or those receiving angiotensin-converting enzyme (ACE) inhibitors, angiotensin receptor blockers (ARBs) or potassium-sparing diuretics. Conversely, other diuretics can increase hypokalemia risk. We assessed the effects of the sodium glucose co-transporter 2 (SGLT2) inhibitor dapagliflozin on serum potassium levels in a pooled analysis of clinical trials in patients with type 2 diabetes mellitus (T2DM). Methods Fourteen randomized, placebo-controlled, double-blind T2DM studies were analyzed: pooled data from 13 studies of ≤24 weeks' duration (dapagliflozin 10 mg, N = 2360; placebo, N = 2295); and one 52-week moderate renal impairment study in patients with baseline eGFR ≥30 to <60 mL/min/1.73 m2 (dapagliflozin 10 mg, N = 85; placebo, N = 84). Central laboratory serum potassium levels were determined at each study visit. Results No clinically relevant mean changes from baseline in serum potassium ≤24 weeks were reported for dapagliflozin 10 mg [−0.05 mmol/L; 95% confidence interval (CI) −0.07, −0.03] versus placebo (−0.02 mmol/L; 95% CI −0.04, 0.00) in the pooled population or in the renal impairment study (−0.03 mmol/L; 95% CI −0.14, 0.08 vs. −0.02 mmol/L; 95% CI −0.13, 0.09, respectively). The incidence rate ratio for serum potassium ≥5.5 mmol/L over 24 weeks for dapagliflozin 10 mg versus placebo was 0.90 (95% CI 0.74, 1.10) in the pooled population; with no increased risk in patients receiving ARBs/ACE inhibitors, or potassium-sparing diuretics, or in those with moderate renal impairment. Slightly more patients receiving dapagliflozin 10 mg had serum potassium ≤3.5 mmol/L versus placebo (5.2% vs. 3.6%); however, no instances of serum potassium ≤2.5 mmol/L were reported. Conclusion Dapagliflozin is not associated with an increased risk of hyperkalemia or severe hypokalemia in patients with T2DM. Funding Bristol-Myers Squibb and AstraZeneca.